Mental Health Screening and Differences in Access to Care among Prisoners. (October 2018) - Martin, Michael S.; Crocker, Anne G.; Potter, Beth K.; Wells, George A.; Grace, Rebecca M.; Colman, Ian
Objective: Disparities in mental health care exist between regional and demographic groups. While screening is recommended as part of a correctional mental health strategy, little work has been done to explore whether it can narrow regional and demographic disparities in access to care. We compared treatment access rates by sex, race, age, and region in relation to screening results. Methods: We conducted a retrospective cohort study using administrative data. All 7965 admissions to the prison system were followed for a median of 14 months. Results: Males and non-Indigenous minority racial groups had lower rates of treatment regardless of screening results; they were less likely both to self-report needs and to receive treatment if these needs were reported. Regional differences revealed higher treatment rates in Atlantic Canada and Ontario, as well as higher rates of inmates self-reporting needs on screening who did not receive treatment in the Atlantic, Québec, and Pacific regions. There were minimal differences between inmates of different age groups. Conclusions: Findings suggest potential resource gaps and/or differences in the performance of screening to detect mental health needs across demographic and regional groups. Screening did not narrow, and may have widened, differences between groups.